STRATEGI BANK SYARIAH DALAM MENGHADAPI INFLASI: PENGARUH NISBAH BAGI HASIL TERHADAP DANA PIHAK KETIGA - Kikin Mutakin (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2024)
This study aims to analyze the strategies implemented by PT. Bank BTPN Syariah Tbk in addressing inflationary pressures and to evaluate the impact of the profit-sharing ratio on the accumulation of third-party funds (TPF). Inflation is often a significant challenge for the banking sector, particularly for Islamic banks that operate on a profit-sharing basis. This research employs a quantitative method with a regression analysis approach to examine the relationship between inflation, profit-sharing ratios, and TPF. The data used includes secondary data from financial reports and macroeconomic statistics over a specific period. The findings indicate that inflation has a significant relationship with TPF, where the profit-sharing ratio plays a critical role in maintaining stability and enhancing customer trust. Strategies such as adjusting profit-sharing ratios and innovating Sharia-compliant products have proven effective in mitigating the effects of inflation. This research is expected to contribute to the development of Islamic banking strategies to enhance competitiveness amid economic dynamics.